2018
DOI: 10.1111/pedi.12672
|View full text |Cite
|
Sign up to set email alerts
|

Insulin resistance is associated with smaller brain volumes in a preliminary study of depressed and obese children

Abstract: There may be a significant cost for developing insulin resistance on the developing brain. Disentangling the precise relationship between the insulin resistance and the developing brain is critical.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…Although the neurobiological mechanisms underlying the relationship between IR and depression have yet to be identified, impairments of brain plasticity have been incriminated. In humans, associations between the severity of IR and the reduction of brain volume have been unveiled (Last et al, 2007;Phillips et al, 2018). In keeping with these results, mice or rats developing IR display deficits in adult hippocampal neurogenesis (Lindqvist et al, 2006;Stranahan et al, 2008;Lang et al, 2009;Park et al, 2010) in a manner similar to that observed in animal models of depression (Surget et al, 2008;David et al, 2009).…”
Section: Introductionmentioning
confidence: 74%
“…Although the neurobiological mechanisms underlying the relationship between IR and depression have yet to be identified, impairments of brain plasticity have been incriminated. In humans, associations between the severity of IR and the reduction of brain volume have been unveiled (Last et al, 2007;Phillips et al, 2018). In keeping with these results, mice or rats developing IR display deficits in adult hippocampal neurogenesis (Lindqvist et al, 2006;Stranahan et al, 2008;Lang et al, 2009;Park et al, 2010) in a manner similar to that observed in animal models of depression (Surget et al, 2008;David et al, 2009).…”
Section: Introductionmentioning
confidence: 74%
“…As obesity is a complex phenomenon, it is important to explore which obesity associated factors are particularly relevant to the brain alterations found in obese/overweight participants. These may include low-grade systemic inflammation ( 43 45 ), HPA dysfunctions ( 46 , 47 ), leptin-resistance ( 48 ), insulin resistance ( 49 51 ), or ceramide-induced DNA methylation ( 52 ). Our findings provide the strongest support for the role of dyslipidemia and systemic inflammation in these brain alteration.…”
Section: Discussionmentioning
confidence: 99%
“…VBM and was positively correlated with insulin sensitivity independent of age, sex, depression severity, and several other clinical factors. 41 In addition, these teenager patients with greater IR index also showed reduced hippocampal and anterior cingulate cortex (ACC) volumes, which were associated with more severe depressive symptoms. 42 These results in teenager studies provided additional information that insulin also play important roles in developing brain and emotional behaviors.…”
Section: Ir and Volumetric Alterationsmentioning
confidence: 99%
“…Adiposity‐related IR was found to be associated with lower cortical thickness across the globe, with the strongest associations locating in the lateral frontal, parietal, and superior temporal cortices. In a group of 46 depressed and obese children, whole brain volume was calculated using VBM and was positively correlated with insulin sensitivity independent of age, sex, depression severity, and several other clinical factors 41 . In addition, these teenager patients with greater IR index also showed reduced hippocampal and anterior cingulate cortex (ACC) volumes, which were associated with more severe depressive symptoms 42 .…”
Section: Brain Atrophymentioning
confidence: 99%